Oral lesions in diabetic patients – role of dental professionals in diagnostics and therapy - Chwalba, Artur; Otto-Buczkowska, Ewa (Journal of Stomatology, 2015)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. It is the result of a deficiency in insulin secretion or an increased cellular resistance to the actions of insulin, leading to a variety of metabolic abnormalities. Persistent hyperglycemia has been associated with the incidence and progression in diabetes-related complications, including oral health problems. Dentists play a major role as part of a therapeutic team in providing oral care to patients with diabetes. Screening for diabetes and prediabetes in the dental office may provide an important benefit to patients. Several studies have demonstrated the beneficial effect of periodontal treatment on metabolic control of diabetic patients.